Effects of the Combination of Nigella Sativa and Mefenamic Acid and Mefenamic Acid Alone on the Severity of Postpartum Pain in Multiparous Women: A Double-Blind Clinical Trial - Maryam Chananeh; Padideh Janati Ataei; Mahrokh Dolatian; Faraz Mojab; Malihe Nasiri (Mashhad University of Medical Sciences, 2018)
Introduction: Postpartum pain or painful uterine contractions is an important postpartum problem, and its relief could improve breastfeeding and mother-infant interactions. Medicinal herbs could be used to relieve postpartum pain with fewer side-effects and better acceptability compared to chemical medications. The present study aimed to compare the effects of the combination of Nigella sativa (Kalonji) and mefenamic acid and mefenamic acid alone on postpartum pain in multiparous women. Materials and Methods: This randomized double-blind clinical trial was conducted on 100 multiparous women with natural delivery, who complained of moderate-to-severe postpartum pain in 2017. The women were randomly assigned to two groups of Kalonji-mefenamic acid (n=50) and placebo-mefenamic acid (n=50). Severity of postpartum pain was measured using the visual analogue scale (VAS) two hours after delivery, and mothers with the pain score of ≥4 were enrolled in the study. Women in the intervention group received mefenamic acid capsules (250 mg) with a Kalonji capsule (500 mg), and the control group received mefenamic acid capsules (250 mg) with a placebo. Severity and duration of pain were measured before and one hour after each medication administration using the VAS. Data analysis was performed in SPSS version 22 using independent and paired t-test, Chi-square, and Mann-Whitney U test. P-value of less than 0.05 was considered statistically significant. Results: Severity of postpartum pain reduced more rapidly and significantly in the Kalonji-mefenamic acid group compared to the placebo-mefenamic acid group (P<0.001). Conclusion: According to the results, combination of Kalonji and mefenamic acid could be used as an effective herbal remedy in the women with postpartum pain.